THE INFLUENCE OF COFFEE TASTE AND TO PRODUCT VARIETY TOWARDS CUSTOMER LOYALTY (STUDY ON COFFEE FROMMAKASSAR COFFEE) - Aldi Pratama Putra; Asdi, Asdi; Aulia, Aulia (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study is a type of quantitative research with the aim of determining the influence of taste and product diversity on customer loyalty study on coffee Darikopi Makassar. Samples were taken from customers of Darikopi Makassar. The type of data used in this study is quantitative data obtained from the results of questionnaires that have been distributed to regular customers of Darikopi Makassar. Data collection is carried out through literature review, questionnaire distribution and documentation. In this study, the data sources used include primary data and secondary data. The research instrument used in this study used the Likert scale method. Based on the results of research using SPSS on the influence of taste and product diversity on customer loyalty of Darikopi Makassar, it was concluded that taste had a positive and significant effect on customer loyalty which was marked by 4,296 > 1.66 with a significance of 0.000. Product diversity has a positive and significant effect on customer loyalty which is marked by 5,785 > 1.66 with a significance of 0.000. Taste and product diversity have an effect of 51.6% on customer loyalty, and simultaneously affect it which is characterized by a probability value of 0.000 < 0.05, Product diversity from Makassar Coffee needs to be maintained and further improved because the results show that product diversity has a more influence than taste on customer loyalty.